Energetic optimization of regenerative braking for high speed railway systems. (1st December 2016) - Frilli, Amedeo; Meli, Enrico; Nocciolini, Daniele; Pugi, Luca; Rindi, Andrea
Highlights: A model of longitudinal dynamics of the High-speed train ETR1000 is presented. The model includes on board traction and braking subsystems. Interactions between overhead line and power line are modelled. The model is validated on real experimental data. An energy storage strategy for a high-speed line is proposed. Abstract: The current development trend in the railway field has led to an ever increasing interest for the energetic optimization of railway systems (especially considering the braking phases), with a strong attention to the mutual interactions between the loads represented by railway vehicles and the electrical infrastructure, including all the sub-systems related to distribution and smart energy management such as energy storage systems. In this research work, the authors developed an innovative coupled modelling approach suitable for the analysis of the energetic optimization of railway systems and based on the use of the new object oriented language Matlab-Simscape™, which presents several advantages with respect to conventional modelling tools. The proposed model has been validated considering an Italian Direct Current High-speed line and the High-speed train ETR 1000. Furthermore, the model has been used to perform an efficiency analysis, considering the use of energy storage devices. The results obtained with the developed model show that the use of energy recovery systems in high-speed railway can provide great opportunities of energy savings.